2014
DOI: 10.1186/2043-7129-2-7
|View full text |Cite
|
Sign up to set email alerts
|

The use of combination of zeolites to pursue integrated refined pyrolysis oil from kraft lignin

Abstract: A mixture of Y and M type zeolites were applied to pyrolyze kraft softwood (SW) lignin with the objective of studying the combination effect of different types of zeolite on pyrolysis. The chemical structures of the subsequent pyrolysis oils were examined. Nuclear Magnetic Resonance (NMR) spectroscopy including 13 C, 31 P of phosphitylated bio-oils, Heteronuclear Single-Quantum Correlation (HSQC)-NMR, and Gel Permeation Chromatography (GPC) were used to characterize the pyrolysis oils. The yields of pyrolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…In addition, a previous study supported that the quantity of every pyrolysis product (heavy oil, light oil, char, and gas) for the combination of the 'Y + M' sample catalyzed pyrolysis remained between the individual Y and M zeolites catalyzed pyrolysis (Huang et al 2014). This phenomenon was observed after the regeneration of each cycle.…”
Section: Pyrolysis Yieldmentioning
confidence: 72%
See 2 more Smart Citations
“…In addition, a previous study supported that the quantity of every pyrolysis product (heavy oil, light oil, char, and gas) for the combination of the 'Y + M' sample catalyzed pyrolysis remained between the individual Y and M zeolites catalyzed pyrolysis (Huang et al 2014). This phenomenon was observed after the regeneration of each cycle.…”
Section: Pyrolysis Yieldmentioning
confidence: 72%
“…No studies have been reported yet to show the catalytic effects of different regeneration times using the combined zeolites and their effect on pyrolysis of lignin. In previous studies, (Huang et al 2014) combined 'Y + M', individual Y and M zeolites were used to catalyze the lignin pyrolysis and the results showed that the combined 'Y + M' sample had a catalytic performance that was in between the individual Y and M zeolites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxyl group types in a wide range of biomass-derived products have been effectively quantified by phosphitylation and 31 P NMR analysis. This analytical technique was first described by Schiff et al in 1986 and then further developed and practically applied by Argyropoulos et al to study lignin and wood chemistry. , In addition to its use in lignin characterization, the above method has also been widely applied in the study of hydroxyl compounds in tannins and flavonoids, , extra-virgin olive oil, biodiesel, pyrolysis oil, hydrothermal liquefaction (HTL) biocrude, and upgraded bio-oil . The quantitative reaction between hydroxyl groups and a phosphitylating agent, such as 2-chloro-4,4,5,5-tetramethyl-1,3,2-dioxaphospholane (TMDP), in the presence of a Brønsted base (Scheme ) has been employed for this purpose. , Reaction of hydroxyl groups with TMDP replaces hydroxyl protons with a nonionizable phosphorus-containing moiety (PO 2 C 6 H 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of papers on catalytic rapid pyrolysis of wood over porous materials have recently been published over the world [11][12][13][14][15][16][17][18][19][20]. Various characteristics of porous materials, for example, quantity and strength of acid sites, surface area, pore size, and crystallinity, have been shown to influence the reforming of bio-oil.…”
Section: Introductionmentioning
confidence: 99%